Inequity in inpatient services utilization: a longitudinal comparative analysis of middle-aged and elderly patients with the chronic non-communicable diseases in China - Xian-zhi Fu; Lian-ke Wang; Chang-qing Sun; Dong-dong Wang; Jun-jian He; Qi-xin Tang; Qian-yu Zhou (BMC, 2020)
Abstract Background Aging and the chronic non-communicable diseases (NCDs) challenge the Chinese government in the process of providing hospitalization services fairly and reasonably. The Chinese government has developed the basic medical insurance system to solve the problem of "expensive medical cost and difficult medical services" for vulnerable groups and alleviate the unfair phenomenon. However, few studies have confirmed its effect through longitudinal comparison. This study aimed to explore the trend in the inequity of inpatient use among middle-aged and elderly individuals with NCDs in China. Methods This longitudinal comparative study was based on CHARLS data in 2011, 2013 and 2015. Concentration index (CI) was used to measure the variation trend of inequity of inpatient services utilization, while the decomposition method of the CI was applied to measure the factors contributing to inequity in inpatient services utilization. The effect of each factor on the change of inequity in inpatient services utilization was divided into the change of the elasticity and the change of inequality using the Oaxaca-type decomposition method. Results The affluent middle-aged and elderly patients with NCDs used more inpatient services than poor groups. The per capita household consumption expenditure (PCE) and Urban Employee Basic Medical Insurance (UEBMI) contributed to the decline in pro-rich inequality of inpatient use, while the New Rural Cooperative Medical Scheme (NRCMS) contributed to the decline in pro-poor inequality of inpatient use. Conclusions There was a certain degree of pro-rich unfairness in the probability and frequency of inpatient services utilization for middle-aged and elderly individuals with NCDs in China. The decrease of pro-wealth contribution of PCE and UEBMI offset the decrease of pro-poor contribution of NRCMS, and improved the equity of inpatient services utilization, favoring poor people.